The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1679-45082014ao3090
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of vitamin D3 in cutaneous melanoma

Abstract: Objective To compare the level of vitamin D3 in cutaneous melanoma patients, with or without disease activity, with reference values and with patients from a general hospital.Methods The serum levels of vitamin D3 were measured in cutaneous melanoma patients, aged 20 to 88 years, both genders, from January 2010 to December 2013. The samples from the general group were processed at Hospital Israelita Albert Einstein (control group). Data analysis was performed using the Statistics software.Results A total of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
1
6
2
2
Order By: Relevance
“…This was possibly, in part due to Filho et al ., which showed, quite different from most other studies, significantly higher vitamin D levels in patients with melanoma than those levels in controls. However, the exclusion and inclusion criteria of controls were not elaborated in this study, and the control group comprised ‘general patients’ instead of healthy controls . This limitation may contribute to substantial bias because a large number of studies have revealed vitamin D deficiency in various diseases .…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…This was possibly, in part due to Filho et al ., which showed, quite different from most other studies, significantly higher vitamin D levels in patients with melanoma than those levels in controls. However, the exclusion and inclusion criteria of controls were not elaborated in this study, and the control group comprised ‘general patients’ instead of healthy controls . This limitation may contribute to substantial bias because a large number of studies have revealed vitamin D deficiency in various diseases .…”
Section: Discussioncontrasting
confidence: 80%
“…Of note, although there was no significant difference in the serum vitamin D levels between patients with melanoma and controls, the heterogeneity of this analysis was extremely high. This was possibly, in part due to Filho et al ., which showed, quite different from most other studies, significantly higher vitamin D levels in patients with melanoma than those levels in controls. However, the exclusion and inclusion criteria of controls were not elaborated in this study, and the control group comprised ‘general patients’ instead of healthy controls .…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Similar condition was also reported by others in AR patients , allergic conjunctivitis , and asthma . Besides allergic disorders, VitD3 abnormality was also found associating with rheumatoid arthritis , diabetes , and cancer .…”
Section: Discussionsupporting
confidence: 89%
“…Results of this study indicate no statistically significant association between serum 25(OH)D levels and melanoma [ 70 ], although there is a suggested protective association in the second quartiles compared to the lowest levels [ 70 ]. Another recent study showed no direct relationship between high or low levels of vitamin D and the occurrence and severity of melanoma [ 71 ]. Furthermore, several studies demonstrated that VDR expression in melanoma cells is more intense than in normal melanocytes [ 72 , 73 ].…”
Section: Vitamin Dmentioning
confidence: 99%